Possible involvement of the μ opioid receptor in the antinociception induced by sinomenine on formalin-induced nociceptive behavior in mice. (23rd April 2019) - Komatsu, Takaaki; Katsuyama, Soh; Takano, Fumihide; Okamura, Takemasa; Sakurada, Chikai; Tsuzuki, Minoru; Ogawa, Kakuyou; Kubota, Atsuhito; Morinaga, Osamu; Tabata, Kenji; Sakurada, Tsukasa
Highlights: Oral administration of sinomenine attenuates formalin-induced nociceptive behavior. Oral administration of sinomenine inhibits ERK activation induced by intra plantar injection of formalin in spinal cord. The analgesic effect of sinomenine may be evoked by μ-opioid receptors. Abstract: Sinomenine, an alkaloid originally isolated from the roots and the rhizome of Sinomenium acutum is used as a traditional Chinese herbal medicines for rheumatoid arthritis and neuralgia. The aims of this study were to investigate the effects of oral administration of shinomenine on formalin-induced nociceptive behavior in mice and the opioid receptor subtypes involved in the antinociceptive effects of sinomenine. Our findings showed that a single dose of oral-administrated sinomenine inhibited the formalin induced licking and biting responses in a dose-dependent manner. Intraperitoneal pretreatment with naloxone hydrochloride, an opioid receptor antagonist, and β-funaltrexamine hydrochloride (β-FNA), a selective μ-opioid receptor antagonist, significantly attenuated sinomenine induced antinociception, but not by naltrindole, a nonselective δ-opioid receptor antagonist and nor-binaltorphimine, a selective κ-opioid receptor antagonist. Furthermore, in western blot analysis, oral administration of sinomenine resulted in a significant blockage of spinal extracellular signal-regulated protein kinase (ERK1/2) activation induced by formalin. Naloxone hydrochloride and β-FNA significantly reversed the blockage of spinal ERK1/2 activation induced by sinomenine. These results suggest that sinomenine-induced anti nociceptive effect and blockage of spinal ERK1/2 activation may be triggered by activation of μ-opioid receptors.